2017
DOI: 10.4067/s0717-95022017000200015
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Muscle Fibers in Rats Submitted to Strength Training and Growth Hormone

Abstract: SUMMARY:The aim of the present study was to observe the changes in the muscle tissue of rats after application of growth hormone (GH) and performing a strength training protocol (ST). In total, 40 male Wistar rats, 60 days old, were used, divided into four groups: control (C), control and application of GH (GHC), strength training (T), and strength training with the application of GH (GHT). The physical training protocol (PT) was composed of four series of 10 jumps in water, 3x/week, with an overload of 50 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This difference in results can be explained by the difference in the predominance of muscle fiber types: the soleus muscle has a predominance of oxidative fibers, whereas the EDL has a predominance of glycolytic fibers; moreover, there is the interference of the biomechanics of movement, for while the soleus muscle is an ankle extensor, the EDL is a toe extender. In this way, the muscles adapted differently to the training, although both demonstrated greater hypertrophy than the animals that performed the aerobic training (Castoldi et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in results can be explained by the difference in the predominance of muscle fiber types: the soleus muscle has a predominance of oxidative fibers, whereas the EDL has a predominance of glycolytic fibers; moreover, there is the interference of the biomechanics of movement, for while the soleus muscle is an ankle extensor, the EDL is a toe extender. In this way, the muscles adapted differently to the training, although both demonstrated greater hypertrophy than the animals that performed the aerobic training (Castoldi et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…The muscle tissue was immersed in n-hexane solution and cooled in liquid nitrogen (-190 ºC), through the freezing method for unfixed tissues, and later stored in an ultra-low temperature freezer (-75 ºC) (Camargo Filho et al, 2011). The 5 mm sections were produced in a cryostat microtome at -20 °C, collected on slides and then stained with hematoxylin-eosin (HE) for immediate analysis of the minimum muscle cell diameter (Castoldi et al, 2017b).…”
Section: Critical Load Test For Determination Of Anaerobicmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16,17 Several authors have demonstrated an increase in the cross-sectional area of muscle fibers from high-intensity, low-volume training. 5,7,18,19 The greater the intensity of the exercise, the greater the stimulus for hypertrophy, promoting greater stimulus to the protein synthesis of the contractile elements responsible for muscle contraction, generating an increase in the volume of muscle fiber. 5,6,17 The muscle hypertrophy process is modulated by the mechanical stimulus to which the muscle tissue is submitted, so an exercise with greater overload will promote greater stimulus for muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effect of physical activity, the animals were submitted to aquatic activity. They were initially submitted to the aquatic activity in a collective tank with 15 cm of depth for 10 minutes, so they could familiarize with the environment and try to remain on the surface (Castoldi et al, 2017). After waiting for 15 minutes, the animals started the aquatic activity in a 40 cm deep tank for 30 minutes, where a load was attached to their back, through vests (Aleixo et al, 2019).…”
Section: Methodsmentioning
confidence: 99%